2015
DOI: 10.1007/s11064-015-1705-z
|View full text |Cite
|
Sign up to set email alerts
|

Competition, Selectivity and Efficacy of Analogs of A-84543 for Nicotinic Acetylcholine Receptors with Repositioning of Pyridine Nitrogen

Abstract: Nicotinic acetylcholine receptors (nAChRs) play a crucial role in a number of clinically relevant mental and neurological pathways, as well as autonomic and immune functions. The development of subtype-selective ligands for nAChRs therefore is potentially useful for targeted therapeutic management of conditions where nAChRs are involved. We tested if selectivity for a particular nAChR subtype can be achieved through small structural modifications of a lead compound containing the nicotinic pharmacophore by cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…a A84543 K i 6 S.E.M. binding data of Abreo et al (1996), Ogunjirin et al (2015) reported K i values of 0.15 and 1 nM for A84543 and nicotine, respectively, at rat brain a4b2 receptors.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…a A84543 K i 6 S.E.M. binding data of Abreo et al (1996), Ogunjirin et al (2015) reported K i values of 0.15 and 1 nM for A84543 and nicotine, respectively, at rat brain a4b2 receptors.…”
Section: Compoundmentioning
confidence: 99%
“…The rat brain a4b2 receptor affinity (Table 6) of trans-59-methylA84543 was 7-fold higher than the cis-59-methylA84543. The rat brain high-affinity receptor K i for A84543 has been reported to be 0.15 6 0.01 (Abreo et al, 1996) and 3.44 6 0.40 nM (Ogunjirin et al, 2015), and the a7 receptor K i was reported to be 340 6 50 nM (Ogunjirin et al, 2015). Although the difference we observed between the two methylated A84543 enantiomers was approximately 10Â less than it was for the 59methylnicotines, it is clear that the preferential binding of the trans-59-methylnicotine also applies to trans-59-meth-ylA85443.…”
Section: Compoundmentioning
confidence: 99%
“…We next selected a set of biologically active complex polyazines to test the base-switching strategy. An analogue of A-84543, a nicotinic acetylcholine receptor agonist, can be selectively converted into phosphonium ion derivatives on each pyridine ring with complete control of regio- and site-selectivity ( 2o ). The tripyridine system in an MK-1064 precursor is a challenging target for site-selective functionalization.…”
Section: Resultsmentioning
confidence: 99%